2016
DOI: 10.1097/wnr.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seizures induced by acute exposure to an organophosphate herbicide, glufosinate-ammonium

Abstract: Glufosinate-ammonium (GLA), the active component of a widely used herbicide, induces convulsions in rodents and humans. In mouse, intraperitoneal treatment with 75 mg/kg GLA generates repetitive tonic-clonic seizures associated with 100% mortality within 72 h after treatment. In this context, we characterized GLA-induced seizures, their histological consequences and the effectiveness of diazepam treatment. Epileptic discharges on electroencephalographic recordings appeared simultaneously in the hippocampus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…3 Although glufosinate ammonium herbicides are considered safe when used properly, 4 many clinical toxicologists have reported that the ingestion of a large amount of glufosinate ammonium can cause convulsions. 5 –8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Although glufosinate ammonium herbicides are considered safe when used properly, 4 many clinical toxicologists have reported that the ingestion of a large amount of glufosinate ammonium can cause convulsions. 5 –8…”
Section: Introductionmentioning
confidence: 99%
“…A combination of clinical studies and in vitro studies has provided a growing consensus that seizure is a common complication of glufosinate herbicide intoxication. 5,11…”
Section: Introductionmentioning
confidence: 99%
“…GA's primary mechanism involves the inhibition of the glutamine synthetase enzyme, resulting in an increase in blood ammonia levels and subsequent damage to various organs, primarily the nervous system, causing tissue necrosis [4][5][6]. However, many patients suffer from sudden respiratory failure, coma, convulsions, and seizures during hospitalization, despite presenting with unremarkable symptoms or signs upon arrival at the emergency department [7][8][9]. Many clinician, particularly emergency physicians, would be hopefully nd out some factors to predict unfavorable outcomes of GA poisoning early.…”
Section: Introductionmentioning
confidence: 99%
“…GA's primary mechanism involves the inhibition of the glutamine synthetase enzyme, resulting in an increase in blood ammonia levels and subsequent damage to various organs, primarily the nervous system, causing tissue necrosis [4][5][6]. However, many patients suffer from sudden respiratory failure, coma, convulsions, and seizures during hospitalization, despite presenting with unremarkable symptoms or signs upon arrival at the emergency department [7][8][9]. Many clinician, particularly emergency physicians, have insu cient knowledge about the harmful effects of GA poisoning.…”
Section: Introductionmentioning
confidence: 99%